The political economy of trade, aid and foreign investment policies - Mitra, Devashish; Panagariya, Arvind (Amsterdam : Elsevier, 2004)
The book is a collection of original essays that not only provide new theoretical insights and empirical evidence into how political an economic forces shape trade policies but break new ground in examining how these forces also influence foreign investment and international aid decisions.
Includes bibliographical references and index.
lje 24/08/16
Loans
Keywords: Mitra, Devashish; Panagariya, Arvind; Commercial policy; International economic relations; Business & Economics; Investments; Foreign investments